Selected Semiconductor Research. - Li, Ming-Fu (World Scientific, 2011)
This unique volume assembles the author's scientific and engineering achievements of the past three decades in the areas of: semiconductor physics and materials, including topics in deep level defects and band structures, CMOS devices, including the topics in device technology, CMOS device reliability, and nano CMOS device quantum modeling, and Analog Integrated circuit design. It reflects the scientific career of a semiconductor researcher educated in China during the 20th century. This book can be referenced by research scientists, engineers, and graduate students working in the areas of sol.